Evaluasi Kinerja Bundaran Simpang Lima Kabupaten Ende - Gare, Mansuetus; Kota, Ireneus (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2020)
In high traffic flows and congestion at intersections, the roundabout is easily blocked, which may causecapacity to be disrupted in all directions. This research study determines the performance of the EndeRegency Intersection five roundabout in current traffic conditions in terms of the level of traffic service, aswell as providing solutions to existing problems at the roundabout which are then used as a basis fordetermining the actions that need to be taken for existing problems. From the research results, it was foundthat the roundabout capacity (C) = 32.67, degree of saturation (DS) = 0.67, delay (DT) = 4.04, queuingopportunity (QPR) = 11.836, travel speed (VO) 30.00, Travel time for the single-line section (TT) = 7.07,which means that the traffic volume at the Simpang Lima roundabout is still tolerable.